Os Odontoideum: an unusual association of compressive synovial cyst. Case report and review of the literature. (3rd June 2015) - Ahmed, AA; Watson, T; Elgheriani, A; Kachur, E; Cenic, A
Abstract : Background: Os odontoideum is a rare cervical abnormality that harbours a potential risk for atlantoaxial instability. In rare circumstances, synovial cysts may develop and compromise the spinal cord. Therefore, cyst excision has been suggested as part of the surgical management. However, in recent reports, it has been shown that atlantoaxial stabilization alone is sufficient for synovial cyst regression. Methodology: 48-year-old woman presented with symptoms and signs of cervical myelopathy secondary to os odontoideum with atlantoaxial instability. A large synovial cyst was diagnosed with significant spinal cord compression. In addition, her spinal and cranial imaging was suggestive of multiple sclerosis which was confirmed clinically thereafter with one episode of MS flare up and positive cerebrospinal fluid analysis. Results: After she had recovered from her MS flare up, posterior atlantoaxial instrumentation and fusion was performed without synovial cyst resection. Postoperatively, her clinical condition improved substantially and complete regression of the synovial cyst was noted on cervical MRI. Interestingly, she has not had any MS recurrent episodes after the surgery. Conclusion: Degenerative changes in os odontoideum are consequences of atlantoaxial instability. Compressive synovial cysts may develop with associated cord compression. We recommend posterior atlantoaxial stabilization alone in such conditions while preserving cyst fenestration or excision for persistent symptoms related to unresolved synovial cysts.